ԱՐՄԵՆ ՄԱՆԱՍՅԱՆ Երիտասարդ դաշնակահարի նվիրյալ գործունեությունը - Արտյոմի Բաբաջանյան, Արսեն (Musical Armenia, 2010)
Review to the Concert: Singer, composer, PhD candidate Arsen Artyomi Babajanyan dedicates his article to young pianist, laureate of Republican and international concerts Armen Manasyan